Studies of the influence of tropospheric factors on the formation of noctilucent clouds by a cartographic method. (April 2020) - Solodovnik, A.A.; Leontyev, P.I.; Dalin, P.
Abstract: The influence of a certain type of tropospheric factors on the appearance and formation of noctilucent clouds at mid-latitudes is studied by utilizing a method of construction and analysis of synthetic weather maps. The method is based on a cartographic comparison of satellite images of large fields of noctilucent clouds over most of northern Eurasia and standard meteorological maps for the same territory. The time of obtained satellite images and meteorological maps coincides within up to half a day. Based on the full set of synthetic weather maps constructed for the 2015 summer season, it is statistically shown that in almost all cases the localization of noctilucent clouds fields is associated with the evolution of a number of typical weather processes in the troposphere. The most pronounced weather processes have been associated with the movement of cyclones and cold fronts, the development of occlusions and extensive thunderstorms. A general explanation of the revealed facts is proposed which is based on the influence of internal gravity waves, arising in the troposphere, on the cloud formation in the upper atmosphere. Prospects for further research on tropospheric-mesospheric interactions are considered. Highlights: Analysis of satellite images, noctilucent clouds and weather maps is proposed. A link between the formation of noctilucent clouds and weather processes is shown. The influence of tropospheric processes can be explained by internal gravitational waves.